Fairfax family papers - Irving, Washington, 1783-1859.
Accounts (1781-1798) of the Fairfax estate; writings; transcripts of letters (1713-1715) of Thomas and Richard Lee to Catherine, Lady Fairfax; "Memoranda of the Fairfax family from Irving's Life of Washington"; wills, deeds, indentures, and other legal documents relating chiefly to Thomas, Lord Fairfax (1693-1781); and history (1932) with photographs of "Belvoir," the Virginia plantation house of Col. William Fairfax (1691-1757).
Microfilm edition available
In part, photocopies and transcripts.
Collection material in English.
Keywords: Fairfax, Thomas Fairfax, -- Lord, -- 1692-1782.; Fairfax, Catherine Culpeper, -- Baroness, -- -1719 -- Correspondence; Fairfax, William, -- 1691?-1757.; Lee, Thomas, -- 1690-1750 -- Correspondence; Lee, Richard, -- 1678-1718 -- Correspondence; Plantations -- Virginia; Washington, George, -- 1732-1799.; Fairfax family